2000
DOI: 10.1007/s002320001089
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Intracellular pH in Human Erythrocytes via K + (Na + )/H + Exchange Under Low Ionic Strength Conditions

Abstract: The change of intracellular pH of erythrocytes under different experimental conditions was investigated using the pH-sensitive fluorescent dye BCECF and correlated with (ouabain + bumetanide + EGTA)-insensitive K(+) efflux and Cl(-) loss. When human erythrocytes were suspended in a physiological NaCl solution (pH(o) = 7.4), the measured pH(i) was 7.19 + or - 0.04 and remained constant for 30 min. When erythrocytes were transferred into a low ionic strength (LIS) solution, an immediate alkalinization increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…However, as has been speculated elsewhere [15,16], it was assumed that the increase of the cation fluxes for RBCs suspended in LIS solutions is mediated by the K It is important to note that, after transferring cells from HIS to LIS solutions, a new steady-state is quickly established, associated with an increase of the internal pH from 7.2 to approximately 7.7 [9] which results in a depolarization from -10 mV to 18.5 mV. Although this calculation (which assumes a Nernst distribution of H + ) will be an underestimation given that in both extracellular and intracellular compartments there will be a significant buffer capacity (the extracellular solution was buffered in the investigations of the low ionic strength effect), the transmembrane potential calculated here for cells in LIS solution is below the level at which significant activation of the NSVDC channel will occur [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as has been speculated elsewhere [15,16], it was assumed that the increase of the cation fluxes for RBCs suspended in LIS solutions is mediated by the K It is important to note that, after transferring cells from HIS to LIS solutions, a new steady-state is quickly established, associated with an increase of the internal pH from 7.2 to approximately 7.7 [9] which results in a depolarization from -10 mV to 18.5 mV. Although this calculation (which assumes a Nernst distribution of H + ) will be an underestimation given that in both extracellular and intracellular compartments there will be a significant buffer capacity (the extracellular solution was buffered in the investigations of the low ionic strength effect), the transmembrane potential calculated here for cells in LIS solution is below the level at which significant activation of the NSVDC channel will occur [4].…”
Section: Discussionmentioning
confidence: 99%
“…The first evidence for the involvement of two separate pathways in the enhancement of unidirectional Na Although it is now recognised that the first pathway is electrogenic [6,7] whereas the latter is electroneutral [8,9], a common pathway underlying these two transport modes cannot be entirely discounted [14]. However, as has been speculated elsewhere [15,16], it was assumed that the increase of the cation fluxes for RBCs suspended in LIS solutions is mediated by the K It is important to note that, after transferring cells from HIS to LIS solutions, a new steady-state is quickly established, associated with an increase of the internal pH from 7.2 to approximately 7.7 [9] which results in a depolarization from -10 mV to 18.5 mV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another indication for the stimulation of the KNHE in response to cooling is the fact that the temperature-sensitive K + influx in the patient's RBC was 6-fold higher when cold exposure studies were performed in low ionic strength medium (data not shown), a condition known to activate KNHE in erythrocytes from healthy humans. 33 Finally, HOE-642, an inhibitor that was shown to suppress KNHE in RBC from healthy donors, 15 blocked both the temperature-sensitive unidirectional K + influx (Table 1) and the K + leak from erythrocytes into plasma by about 50% when the patient's blood was exposed to cold ( Figure 2B). All these data indicate that an abnormally high activity of KNHE accounts, in part, for the high cation permeability of CHC RBC.…”
mentioning
confidence: 95%
“…For this reason 5 µM nigericin was added to RBCs suspended in the calibration buffer solutions containing 135 mM KCl, 10 mM NaCl, 10 mM glucose, 10 mM HEPES/NaOH [11,12]. The calibration curve was linear in the pH range 6.5-8.0.…”
Section: Calibration For Ph I Determinationmentioning
confidence: 99%